PERANAN SRABI SEBAGAI MAKANAN KHAS UNTUK MEPERTAHANKAN NILAI KEARIFAN LOKAL - Tri Rinawati; Rita Meiriyanti; Diana Puspitasari (Jurnal Dinamika Sosial Budaya, 2017)
Local wisdom about traditional food contained in the archipelago, especially the Javanese script is a legacy of high-value ancestors because by inheriting the tradition of food, can strengthen the identity and identity of the Indonesian nation universally.This research uses qualitative method with phenomenology approach. Data collection is done on observation (participant observation), in depth interview (in depth interview) and documentation. Data analysis is data reduction, display data and conclusion drawing / verification. Test the credibility of the data with triangulation and member check. The potential of srabi as a typical food in Ngampin Ambarawa Village is as a source of family income. The traders srabi get additional income by selling the srabi. Sales turnover will increase during holidays and during celebrations of the familiar traditions of Sha'ban moon better known as "Sha'banan". Efforts to preserve srabi in the village of Ngampin Ambarawa is by continuing to preserve local wisdom of local culture, eg Srabinan tradition which was held during the month of Sha'ban especially on 13, 14 and 15. The role of local government (PEMDA) continues to provide guidance to the traders of srabi traders, so that traders can continue to maintain the existence of srabi at any time. Making srabi as a special food Ngampin Ambarawa village as an effort to maintain the value of local wisdom.